2015
DOI: 10.3892/ol.2015.3575
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of chemotherapeutic efficacy using the ratio of neutrophils to lymphocytes in patients with unresectable or recurrent gastric cancer

Abstract: Abstract. In cancer patients, the balance between neutrophil (N) and lymphocyte (L) cell counts fluctuates with the tumor load. The objective of the present study was to determine the implications of the chemotherapy effect by the fluctuations of N/L ratio in patients with unresectable or recurrent gastric cancer. The study participants were identified from a prospective cohort of patients with unresectable or recurrent gastric cancer (n=135). The median N/L ratio was 3.23 (range: 0.76-20.45) prior to chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“… 32 The variation between the pre-chemo- and post-chemo-NLR may illustrate the effects of chemotherapy in unresectable or recurrent gastric cancer. 33 Regarding the prognoses of many malignancies, including respiratory, gastrointestinal, hepatobiliary, gynecological, and urinary cancers, the NLR has been shown to deal with it effectively. The pretreatment NLR in patients with combined small-cell lung cancer was not only strongly associated with the stage of disease and tumor recurrence but could also predict the relapse-free survival and OS as an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“… 32 The variation between the pre-chemo- and post-chemo-NLR may illustrate the effects of chemotherapy in unresectable or recurrent gastric cancer. 33 Regarding the prognoses of many malignancies, including respiratory, gastrointestinal, hepatobiliary, gynecological, and urinary cancers, the NLR has been shown to deal with it effectively. The pretreatment NLR in patients with combined small-cell lung cancer was not only strongly associated with the stage of disease and tumor recurrence but could also predict the relapse-free survival and OS as an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis to investigate the association between the NLR and the prognosis of gastric cancer revealed that a high preoperative NLR is associated with poor survival in patients with gastric cancer (16). Several studies have demonstrated that the NLR is a prognostic and predictive biomarker in patients with advanced gastric cancer (17)(18)(19)(20)(21). Yamanaka et al (17) revealed that the NLR is an independent prognostic factor in advanced gastric cancer patients undergoing palliative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, investigators have demonstrated that the presence of a systemic inflammatory response and the preoperative immunonutritional status are associated with a poor prognosis in patients with various types of cancer (2)(3)(4)(5). The Glasgow Prognostic Score (GPS) (5)(6)(7)(8)(9)(10)(11)(12), the Prognostic Nutritional Index (PNI) (13)(14)(15), the neutrophil lymphocyte ratio (NLR) (10,(16)(17)(18)(19)(20)(21), the platelet lymphocyte ratio (PLR) (21)(22)(23)(24) and the controlling nutritional status (CONUT) (25)(26)(27) have been reported to have prognostic value in patients with many types of cancer. Some studies have demonstrated that these inflammatory and nutritional factors may predict the prognosis of patients with advanced gastric cancer (10)(11)(12)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…A series of studies measured NLR before initiating the 1st-line chemotherapy ( 22 , 23 ), but NLR is not a fixed value and fluctuates with the patient's condition. Wang et al reported that the OS of unresectable GC patients whose NLR levels increased after the 1st-line treatment was nine months, whereas that of patients with decreased NLR was 20 months ( 24 ).…”
Section: Discussionmentioning
confidence: 99%